Aquaporins in sperm osmoadaptation: an emerging role for volume regulation - Chen Qi; Duan En-kui (Acta Pharmacologica Sinica, 2016)
Upon ejaculation, mammalian sperm experience a natural osmotic decrease during male to female reproductive tract transition. This hypo-osmotic exposure not only activates sperm motility, but also poses potential harm to sperm structure and function by inducing unwanted cell swelling. In this physiological context, regulatory volume decrease (RVD) is the major mechanism that protects cells from detrimental swelling, and is essential to sperm survival and normal function. Aquaporins are selective water channels that enable rapid water transport across cell membranes. Aquaporins have been implicated in sperm osmoregulation. Recent discoveries show that Aquaporin-3 (AQP3), a water channel protein, is localized in sperm tail membranes and that AQP3 mutant sperm show defects in volume regulation and excessive cell swelling upon physiological hypotonic stress in the female reproductive tract, thereby highlighting the importance of AQP3 in the postcopulatory sperm RVD process. In this paper, we discuss current knowledge, remaining questions and hypotheses about the function and mechanismic basis of aquaporins for volume regulation in sperm and other cell types.